Fractionation of Golgi, Endoplasmic Reticulum, and Plasma Membrane from Cultured Cells in a Preformed Continuous Iodixanol Gradient - John Graham (The Scientific World Journal)
A continuous iodixanol gradient within the range 0-30% (w/v) iodixanol can resolve the major membrane compartments of the endoplasmic reticulum, Golgi membranes, and plasma membrane from a postnuclear supernatant prepared from a cultured cell homogenate. The precise density range of the gradient and the centrifugation conditions (100,000-200,000 g for 2-16 h) vary with the type of cell and the requirements of the separation. The strategy is widely used to study the processing of proteins within cells.